Why Would the Brain Need Dormant Neuronal Precursors? - Benedetti, Bruno; Couillard-Despres, Sebastien (Frontiers in Neuroscience, 2022)
Dormant non-proliferative neuronal precursors (dormant precursors) are a unique type of undifferentiated neuron, found in the adult brain of several mammalian species, including humans. Dormant precursors are fundamentally different from canonical neurogenic-niche progenitors as they are generated exquisitely during the embryonic development and maintain a state of protracted postmitotic immaturity lasting up to several decades after birth. Thus, dormant precursors are not pluripotent progenitors, but to all effects extremely immature neurons. Recently, transgenic models allowed to reveal that with age virtually all dormant precursors progressively awaken, abandon the immature state, and become fully functional neurons. Despite the limited common awareness about these cells, the deep implications of recent discoveries will likely lead to revisit our understanding of the adult brain. Thus, it is timely to revisit and critically assess the essential evidences that help pondering on the possible role(s) of these cells in relation to cognition, aging, and pathology. By highlighting pivoting findings as well as controversies and open questions, we offer an exciting perspective over the field of research that studies these mysterious cells and suggest the next steps towards the answer of a crucial question: why does the brain need dormant neuronal precursors?